University Physics Volume 3 - Sanny, Jeff; Ling, Samuel; Open Textbook Library (Open Textbook Library, 2016)
University Physics is a three-volume collection that meets the scope and sequence requirements for two- and three-semester calculus-based physics courses. Volume 1 covers mechanics, sound, oscillations, and waves. Volume 2 covers thermodynamics, electricity and magnetism, and Volume 3 covers optics and modern physics. This textbook emphasizes connections between between theory and application, making physics concepts interesting and accessible to students while maintaining the mathematical rigor inherent in the subject. Frequent, strong examples focus on how to approach a problem, how to work with the equations, and how to check and generalize the result.
Unit 1: Optics -- Chapter 1: The Nature of Light -- Chapter 2: Geometric Optics and Image Formation -- Chapter 3: Interference -- Chapter 4: Diffraction -- Unit 2: Modern Physics -- Chapter 5: Relativity -- Chapter 6: Photons and Matter Waves -- Chapter 7: Quantum Mechanics -- Chapter 8: Atomic Structure -- Chapter 9: Condensed Matter Physics -- Chapter 10: Nuclear Physics -- Chapter 11: Particle Physics and Cosmology
In English.
Description based on online resource
Keywords: Science -- Textbooks; Physics -- Textbooks